Geology and Geohydrology of the South Monghyr Region, Bhagalpur Division, Bihar - Rai, SS; Dayal, R. (Journal of Soil and Water Conservation, 2022)
The south Monghyr region as described in this paper comprises of Sadar and Jamui subdivisions of Monghyr district in Bhagalpur division. The area extends between 24.22, and 25. 25' north latitudes and 85. 54' and 86.44. east longitudes. It covers about 3500 sq. miles on one inch to one mile topograbhic sheet nos. 72/G/15,16, 72 11/13, 72 104, 7,8,11,12, 72, L/1,2,5,6,7,9 and 10 and extends some 50 miles from east to west and 70 miles from north to south.